Overlapping climate clubs: Self-enforcing R&D networks to mitigate global warming - Emilson C. D. Silva; Chikara Yamaguchi (Games, 2022)
Free riding incentives make it difficult to control climate change. To improve the chances of the Paris Agreement's ambitious goal, many nations are forming scientific networks in carbon capture and storage (CCS). These networks take many forms (bilateral, hub-and-spoke, and multilateral). Studies of social interactions among scientists demonstrate that research networks are limited because of relational issues, such as lack of trust. This paper provides a rationale for the formation of various types of international CCS networks and examines their impacts on climate change. Our concept of stability focuses on Nash equilibria that are immune to coalitional deviations in overlapping networks. Players may belong to various research networks. A particular research network is a climate club. We show that in the absence of top-down coordination in clubs, the type of global network that forms depends on relational attrition. The complex task is to mitigate free riding while enhancing trust.
Keywords: 330; carbon capture and storage; climate clubs; coalition-proof equilibrium; global warming; hub-and-spoke; international environmental agreements; overlapping coalitions